Correlation of intra operative specimen imaging with final histopathology in breast conserving surgery for breast cancer - Javed, Nida; Afzal, Sidra; Parvaiz, Muhammad Asad; Rehman, Bushra; Bin Khalid, Ibtissam (Journal of the Pakistan Medical Association, 2024)
Objectives: To determine the effectiveness of specimen mammography in breast conserving surgery cases with respect to reduction in margin positivity rate, and to see whether the rate of secondary surgeries is decreased by intra-operative excision based on specimen mammography evaluation. Method: The retrospective study was conducted at the Shaukat Khanum Memorial Cancer Hospital and Research Centre, Lahore, Pakistan, and comprised data from January 2018 to December 2019 related to all female breast cancer patients who underwent mastectomy or breast conserving surgery with the involvement of specimen mammography. Sensitivity, specificity, positive predictive value and negative predictive value of specimen mammography were calculated. Data was analysed using SPSS 20. Results: Of the 226 patients initially assessed, 65(28.7%) were excluded, and the final sample comprised 161(71.2%) women with mean age 46.71±10.47 years. The sensitivity, specificity, positive predictive value and negative predictive value of specimen mammography for the sample were 65.8%, 80.8%, 54% and 87.3%, respectively. Performing specimen mammography for intra-operative margin assessment in 12 patients was likely to spare 1 patient from re-excision. Conclusion: Intra-operative specimen mammography was found to be a reliable tool for assessing margin status. Key Words: Breast cancer, Specimen mammography, Breast conservation surgery, Margin positivity.